Pengaruh Model Pembelajaran Think Talk Write (TTW) Terhadap Keterampilan Menulis Karangan Teks Nonfiksi Kelas 5 - Nafa Pravita Zalianty; Ismail Marzuki (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Writing skills are one of the four language skills acquired by students. In the 5th-grade class at MI Muhammadiyah 1 Gumeno, there is an issue where students take a long time to complete writing compositions and struggle to arrange words. One solution to address this problem is the implementation of the Think Talk Write (TTW) learning model. This study aims to determine the effect of the Think Talk Write (TTW) learning model on the nonfiction text writing skills of 5th-grade students. The research was conducted using a quantitative approach with a weak experimental design (Pre-Experiment) involving only one treatment group without a control group. The subjects of this study were all 14 5th-grade students at MI Muhammadiyah 1 Gumeno. The data collection technique used was testing, consisting of pre-tests and post-tests. Based on the results of the paired sample t-test, the Sig. (2-tailed) value was 0.000 < 0.05, which means that H0 is rejected and Ha is accepted. These findings indicate that the Think Talk Write (TTW) learning model has a significant effect on the nonfiction text writing skills of 5th-grade students